2013
DOI: 10.1002/hup.2365
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 beta gene and risk of schizophrenia: detailed case–control and family‐based studies and an updated meta‐analysis

Abstract: The present study does not support a role for IL1B in schizophrenia susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Allelic or genotypic association between the IL-1β C-511T polymorphism and schizophrenia was reported by case-control as well as family studies (110,111). Other studies have reported no significant association between the IL-1β C-511T or IL-1β C3954T SNP and schizophrenia (112), which disagrees with a meta-analysis in a specific population that reported a moderate association of IL-1β C-511T and C3954T polymorphisms with schizophrenia in Caucasian samples, suggesting that the genetic effect of IL-1β on schizophrenia may be ethnicity dependent (113).…”
Section: Cytokine Polymorphisms In Schizophreniamentioning
confidence: 99%
“…Allelic or genotypic association between the IL-1β C-511T polymorphism and schizophrenia was reported by case-control as well as family studies (110,111). Other studies have reported no significant association between the IL-1β C-511T or IL-1β C3954T SNP and schizophrenia (112), which disagrees with a meta-analysis in a specific population that reported a moderate association of IL-1β C-511T and C3954T polymorphisms with schizophrenia in Caucasian samples, suggesting that the genetic effect of IL-1β on schizophrenia may be ethnicity dependent (113).…”
Section: Cytokine Polymorphisms In Schizophreniamentioning
confidence: 99%
“…Genome-wide association studies have revealed genetic polymorphism of immune-related genes in SCZ etiopathophysiology. For example, genetic polymorphisms of C4 complement factor, major histocompatibility complex (MHC) locus on chromosome 6 ( Shi et al, 2009 ; Sekar et al, 2016 ), interleukin-1β, IL-6, the soluble IL-6 receptor (sIL6R), and IL-10 are associated with increased risk of SCZ ( Xu and He, 2010 ; Gao et al, 2014 ; Shibuya et al, 2014 ; Hudson and Miller, 2018 ). In contrast, polymorphism of IL-2, IL-4, tumor necrosis factor-α (TNF-α), or transforming growth factor- β1 (TGF-β1), are not associated with increased risk of SCZ ( Qin et al, 2013 ; Hudson and Miller, 2018 ).…”
Section: Altered Gut Microbiota Inflammation and Neurodevelopmental D...mentioning
confidence: 99%
“…Yet, another study found increased secretion of IL-1β from monocytes derived from individuals with schizophrenia, which normalizes with antipsychotic medication treatment [52][53][54]. A meta-analysis from 8724 case-control and 201 samples from 16 studies failed to identify an association between IL1β C511T single nucleotide polymorphism (SNP) of the IL-1β gene and schizophrenia [55]. However, a study in a different population found that the IL1β C-511T and C395T polymorphisms were moderately associated with schizophrenia in a group of Caucasian individuals [56], suggesting that the relationship might be specific only to certain racial or ethnic groups.…”
Section: Interleukin 1 Beta (Il-1β)mentioning
confidence: 99%